Improving Speaking Fluency through Project-Based Learning in Online EFL Classrooms - Vena Amoris; Neria Anetotia Sitarda (Journal of Applied Linguistics and Language Practice, 2025)
This study explores the implementation of Project-Based Learning (PBL) to enhance speaking fluency among students learning English as a Foreign Language in online classrooms. The research was motivated by the persistent challenges learners face in expressing ideas fluently and confidently during virtual English sessions. A qualitative descriptive method was employed involving observation, interviews, and speaking performance assessments to gain a comprehensive understanding of students’ progress. The participants were university-level English learners who engaged in online project-based tasks focusing on real-life communication and problem-solving activities. The findings indicated that PBL effectively improved students’ speaking fluency through increased opportunities for interaction, collaboration, and authentic language use. Moreover, students reported higher motivation and confidence as they worked collaboratively to plan, design, and present their projects in English. The use of PBL also encouraged learner autonomy and creativity, fostering active participation and meaningful learning experiences even in a virtual environment. The study concludes that integrating Project-Based Learning into online English instruction promotes not only linguistic fluency but also critical thinking and social skills necessary for academic and professional communication. These findings highlight the pedagogical value of PBL as an innovative approach for developing speaking fluency in online language learning contexts.